2007
DOI: 10.1002/pbc.21034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pediatric palliative care educational workshop for oncology fellows

Abstract: Fellows reported open beliefs about palliative care, but acknowledged weaknesses in their training and level of competence. The workshop showed efficacy in improving knowledge, but additional research is needed to evaluate larger educational initiatives and their long-term impact on clinical services and family satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 31 publications
1
35
0
1
Order By: Relevance
“…This finding is consistent with previous studies in health care professionals [33][34][35][36][37][38][39][40][41] . Liben and colleagues previously reported that healthcare professionals often rely upon colleagues for support more than their family and friends 45 , whereas we found that GPs generally receive support from own family members and-to a lesser extent-their colleagues.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…This finding is consistent with previous studies in health care professionals [33][34][35][36][37][38][39][40][41] . Liben and colleagues previously reported that healthcare professionals often rely upon colleagues for support more than their family and friends 45 , whereas we found that GPs generally receive support from own family members and-to a lesser extent-their colleagues.…”
supporting
confidence: 94%
“…Several studies reported how providing pediatric palliative care affects health care professionals [33][34][35][36][37][38][39][40][41] . Thus, we hypothesized that providing home-based palliative care to a child with incurable cancer is likely a challenging task for many GPs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Our research has confirmed that oncologists are not well-trained to have these difficult EOL conversations, and ongoing education is needed to sustain knowledge of palliative care (Baughcum, Gerhardt, Young-Saleme, Stefanik, & Klopfenstein, 2007;Gerhardt et al, 2009). As a result, referrals to palliative care or hospice often occur late in the disease process or not at all.…”
Section: Mid-career: Pearl 5-network and Collaboratementioning
confidence: 86%
“…20 Participants completed informed consent and questionnaires before the workshop, which addressed special issues in pediatrics, pain management, symptom management, ethics, communication, and grief=bereavement. Follow-up questionnaires were completed online at 6 and 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…17 This pilot study longitudinally evaluated a 1-day workshop on palliative and EOL care for pediatric hematology= oncology fellows. 20 We assessed participants' reports of barriers, attitudes, and knowledge regarding pediatric palliative care over one year. We expected fellows would: (1) perceive fewer barriers, (2) report more competence, comfort, and open attitudes, and (3) maintain gains in knowledge of palliative care over time.…”
Section: Introductionmentioning
confidence: 99%